Admission Hypothermia Among Neonates Presented to Neonatal Intensive Care Unit - Akter, Shaheen; Parvin, Rubiya; Yasmeen, B.H. Nazma (Journal of Nepal Paediatric Society, 2013)
Introduction: In developing countries, thermal protection of the newborn is not properly addressed. Neonates presented to Neonatal intensive care unit (NICU) for admission with various problems are frequently found to be hypothermic. The objective of this study was to determine the incidence and associated risk factors for neonatal hypothermia on admission to NICU. Materials and Methods: This was a prospective observational study carried over a period of three years at Enam Medical College and Hospital (EMCH) among the newborns admitted to NICU. Hypothermia has been defined as axillary temperature <36.5°C (<97.7° F). Temperature was measured at admission. Data were collected regarding perinatal and socio economic factors. Bivariate and multivariate analysis has been done to see the association of risk factors. Result: A total of 2310 babies between 0 and 680 h of age (mean 43± 12 hours) were studied. Thirty four percent (785) of the neonates had hypothermia. Mean gestation was 34±3 weeks and 42.5% were inborn. Significant determinants of neonatal hypothermia at admission included factors like preterm (p=0.03), low birth weight (p=0.005), normal delivery (p=0.012), birth asphyxia (p=0.001) below average socioeconomic status (p=0.001) and long distance (>10 km) travelled by the neonate (p=0.03). Independent variables are resuscitation at birth [p=.001, Odds Ratio (OR), 2.43; Confidence Interval (CI), 1.47 to 4.00], (p=0.001), age less than 24 hours (p=.02; OR 2.25; CI, 1.13 to 4.47), low birth weight (p=0.03; OR,2.0; CI, 1.06 to 3.82), caesarean section(C/S) delivery (p=.006; OR 1.35; CI, 1.18-2.12) and below average economic status (p=0.001; OR, 2.76; CI, 1.56 to 5.90). Conclusion: Incidence of admission hypothermia among neonates in our NICU was 34%. Independent risk factors are resuscitation at birth, very low birth weight, C/S delivery, age less than 24 hours and poor socio-economic condition. Proper thermal care should be provided for neonates both at home and hospitals. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8312 J. Nepal Paediatr. Soc. 2013;33(3):166-171